2011
DOI: 10.1002/lary.21370
|View full text |Cite
|
Sign up to set email alerts
|

Principles of inner ear sustained release following intratympanic administration

Abstract: The inner ear pharmacokinetic profile of drugs administered intratympanically is not only highly dependent upon the nature of the vehicle but also upon the physicochemical properties of the drug delivered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
63
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 20 publications
(17 reference statements)
6
63
0
Order By: Relevance
“…The intratympanic administration of OTO-104 has been extensively studied both nonclinically [Wang et al, 2009[Wang et al, , 2011aPiu et al, 2011] and clinically [Lambert et al, 2012] in various species. It was not associated with adverse effects at doses that achieved sustained inner ear exposure both locally in the ear as well as systemically in animal studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intratympanic administration of OTO-104 has been extensively studied both nonclinically [Wang et al, 2009[Wang et al, , 2011aPiu et al, 2011] and clinically [Lambert et al, 2012] in various species. It was not associated with adverse effects at doses that achieved sustained inner ear exposure both locally in the ear as well as systemically in animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that dexamethasone formulated using a poloxamer hydrogel provides lasting exposure in the inner ear of guinea pigs and sheep for weeks to months with a single intratympanic injection [Wang et al, 2009[Wang et al, , 2011a. A proprietary otic formulation, OTO-104, was well tolerated locally and systemically in extensive toxicology studies conducted in guinea pigs .…”
Section: Introductionmentioning
confidence: 99%
“…Other potential round window delivery systems that could be evaluated in this fashion include poloxamer (40,41), as well as other aqueous solution-based systems (37,42). In addition, other approaches that directly introduce compounds into perilymph, whether through the round window or through a cochleostomy, may also be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Such results are consistent with the short residence time of dexamethasone in the inner ear compartment when administered as a solution intratympanically. In guinea pigs, a DSP solution is cleared rapidly, with drug levels in the perilymph lasting for about 12 h [Wang et al, 2009[Wang et al, , 2011a. Therefore, the therapeutic potential of dexamethasone is best achieved when the drug can remain present in the inner ear compartment for extended periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a dexamethasone solution is cleared rapidly from the middle ear down the Eustachian tube, with drug levels in the perilymph lasting for about 12 h in guinea pigs [Wang et al, 2009[Wang et al, , 2011a. In the clinic, inconsistent clinical responses are commonly observed due to variable and limited exposure with aqueous solutions [Bird et al, 2007[Bird et al, , 2011.…”
mentioning
confidence: 99%